Comparison of short-term outcome between modified extraperitoneal uterosacral ligament fixation (MEUSL) and sacrospinous ligament fixation (SSF) for apical vaginal support - Mat Noh, Nurul Hikmah; Nusee, Zalina; Ismail, Rozihan; Mohd Taha, Riduan (EUROPEAN OPEN SCIENCE, 2025)
Prevention of apical prolapse during prolapse surgery is crucial to ensure a good outcome of the surgery. The choice of the best method for apical support remains debatable. This is a study comparing the surgical outcome between modified extraperitoneal uterosacral ligament fixation (MEUSL) and sacrospinous ligament fixation (SSF). This is a case-control study involving 42 patients with stage three and four pelvic organ prolapse (POP) looking into surgical failure, prolapse recurrence, lower urinary tract symptoms (LUTS), and operative complications. The results were analyzed using an independent t-test for normally distributed continuous data and a chi-square test for categorical data. A logistic regression analysis was also performed to predict the outcome. A p-value of <0.05 was deemed significant. MEUSL is less likely to have surgical failure at six months with an OR of 7.25 (p = 0.03, CI 1.24–42.38). There is no difference in terms of lower urinary tract symptoms. Intraoperatively, MEUSL had a significantly higher blood loss as compared to the SSF group. MEUSL is an effective technique for the treatment of apical prolapse as it has a lower risk of surgical failure as compared to SSF. A future study regarding long-term outcomes between the two procedures is recommended to guide surgeons in choosing the best treatment option